2017
DOI: 10.1159/000485904
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Activation of the Wnt/β-Catenin Pathway by Bone Marrow Stem Cell Attenuates Cisplatin-Induced Kidney Injury

Abstract: Background/Aims: Cisplatin-induced acute kidney injury (AKI) involves damage to tubular cells via excess reactive oxygen species (ROS) generation. Stem cell-based therapies have shown great promise in AKI treatment. In this study, we aimed to assess the protective effect and mechanism of bone marrow mesenchymal stem cell (BMSC)-derived conditioned medium (CM) against cisplatin-induced AKI. Methods: In vitro, NRK-52E cells were incubated with cisplatin in the presence or absence of CM, followed by the assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…In addition, berberine reduces circulating microparticles, inhibits apoptosis of leukocyte-mediated endothelium [14], activates peroxisome proliferator-activated receptor gamma (PPARγ) and suppresses oxidative stress [15,16], ameliorates vascular permeability and increases tight junction by the upregulation of claudins (e.g., claudin-5) [17]. In the present study we aimed to investigate whether berberine might protect GVB via the modulation of the Wnt/beta-catenin signaling pathway, which can be blocked by inhibitor ICG001 both in vivo and vitro experiments [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, berberine reduces circulating microparticles, inhibits apoptosis of leukocyte-mediated endothelium [14], activates peroxisome proliferator-activated receptor gamma (PPARγ) and suppresses oxidative stress [15,16], ameliorates vascular permeability and increases tight junction by the upregulation of claudins (e.g., claudin-5) [17]. In the present study we aimed to investigate whether berberine might protect GVB via the modulation of the Wnt/beta-catenin signaling pathway, which can be blocked by inhibitor ICG001 both in vivo and vitro experiments [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The cells were cultured in the presence of CARsomes for 24 hours with cisplatin to test their responsiveness to apoptosis inducer. We observed that exposure to cisplatin (a nonspecific apoptosis inducer 13 expression is a specific feature of Ag-specific T-cell activation. 12 The results demonstrate that CARsomes can specifically induce Agspecific Th2 cell apoptosis.…”
Section: Carsomes Induce Ag-specific Th2 Cell Apoptosismentioning
confidence: 95%
“…7 show that b-catenin and cyclin D1 levels were decreased in HepG2SF1 and Huh7SF1 cells compared to their parental cells, while they were increased in AMPKtransfected cells. It has been demonstrated that b-catenin, through repression of the transcription factor TCF7L2, upregulates the expression of peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1a), which has been shown to be involved in hepatocyte differentiation (Jiao et al, 2017;Wanet et al, 2017). In contrast, AMPK can directly phosphorylate and activate PGC-1a and regulate its expression (Colombo and Moncada, 2009).…”
Section: Potential Mechanisms Involved In the Ampk Effectmentioning
confidence: 99%